(untitled) (Journal of Philosophy Culture and Political Science, 2018)
The article seeks to uncover the theoretical and methodological part of the study of human problems. Conducted historical and philosophical analysis in the field of philosophical and religious anthropology, since its formation until the twentieth century. Carried out expert analysis of the religious situation in independent Kazakhstan and a conclusion regarding its critical parties and shows, what is the relationship with the problem of man. Also indicates that the study of human problems in the present time is closely connected with such phenomena as religion, its place in society and in human life. It is now widely extends the idea of multi-religious unity and interreligious peace, which is the only effective way of preserving peace, arising from the needs of modern civilization, learn from small conflicts and big wars, resulting from the historical inconsistencies of religious views. This is necessary in order to prevent conflicts and wars in the future. So, in order to establish a policy of inter-religious peace and peaceful coexistence of religions, to identify what philosophical insights on religion and man, its spiritual values and tolerance is one of the crucial sought after issues of this time. Key words: religious philosophy, religious faith, religious fanaticism, spiritual uplift, anthropological reflections, a spirit, a wise man, a mature man, the life, the soul of man, the power.